(untitled) (International Journal of Current Engineering and Technology, 2013)
The paper shows the Experimental study of the performance of the PEM fuel cell with varying mass flow rate of hydrogen and oxygen. It also focuses the effect of fuel cell temperature on the performance of the fuel cell. Fuel cell performance is increased by proper water management on the membrane. Basic parameter which enhances the fuel cell performance is Relative humidity, Flow Field design, Temperature, Stoichiometric ratio. With the help of this studies, we observe that the fuel cell performance improve by Increasing the relative humidity, temperature, pressure, stoichiometric ratio and using the split serpentine flow field instead of single serpentine flow field. The effects of different fuel cell operating temperatures and mass flow rates on the performance of proton exchange membrane (PEM) fuel cell have been studied experimentally, using pure hydrogen on the anode side and air on the cathode side. The objective of this study is to explore the research in the field of PEM fuel cell and to make it cost effective for sustainable power supply.z